Approaches for strengthening causal inference regarding prenatal risk factors for childhood behavioural and psychiatric disorders. (5th September 2013) - Lewis, Sarah J.; Relton, Caroline; Zammit, Stanley; Smith, George Davey
Abstract : Background: The risk of childhood behavioural and psychiatric diseases could be substantially reduced if modifiable risk factors for these disorders were identified. The critical period for many of these exposures is likely to be in utero as this is the time when brain development is most rapid. However, due to confounding and other limitations of traditional epidemiological studies, identification of causal risk factors has proved challenging and on the whole research in this area has not been fruitful. Scope: In this review, we highlight several alternative approaches including; comparisons across settings, the use of negative controls and natural experiments, which includes migration studies, studies of individuals conceived using in vitro fertilisation and not least Mendelian randomisation. We have illustrated these approaches using examples of behavioural and psychiatric disorders. Conclusion: By having these approaches outlined together in one review, researchers can consider which of these methods would be most suitable for their study question. We have particularly focussed on Mendelian randomisation, as this is a relatively novel concept, in doing so, we have illustrated the concept and discused the implementation and the limitations of this approach.